The Experience of diagnosis and time of chemotherapy of women with breast cancer : A Meta-aggregative review - Kellerer, Jan Daniel; Haun, Magdalena; Rohringer, Matthias (Advances in Social Sciences Research Journal, 2021)
Breast cancer is one of the most prevalent malignancies in women worldwide and affects all dimensions of health. The aim of this meta-aggregative review is to describe the experience of diagnosis and the subsequent period of therapy of women with breast cancer. Following a systematic literature research, ten publications were included in the meta-aggregative review and the study results were synthesized by categorization. Emotional burden, challenges, psychosocial support, and individual coping strategies were described by affected women, and disease-related information sharing and fulfilment of expectations in health professionals were experienced as unsatisfactory. There is a need for improvement in the context of information and counseling measures by health professionals.